Numerical–Experimental Analysis to Optimize the Geometry of a Prosthetic Abutment - Giovanni M. Grasso; Marco Bonfanti; Damiano Alizzio; Fabio Lo Savio (Applied Sciences)
This paper aims to identify methods for optimizing the geometry of dental prosthesis preparation, through both an analytical study and a numerical investigation. Assuming a 10° inclined load with respect to the median sagittal plane, a double algorithm was developed that was capable of calculating the axial resistance area and the cusp resistance area (if present) of a prosthetic abutment as the main geometric parameters vary. In particular, a coupling model with a pseudo-elliptical base was proposed, which is better than the circular shape representing the real shape assumed by the abutment following the dental intervention. The model also allows the presence of a cusp. This model was first analyzed using FEA, also simulating the presence of coupling cement between the abutment and the crown, and then physically made with a 10:1 scale prototype. The convergence of the experimental results found with the numerical–theoretical studies is an indication of the validity of the proposed model. A key contribution of this research using the proposed algorithm allowed to demonstrate that a superior limit of 0.25 for the ratio (HR) between the heights of the cusp sulcus (h-hc) and the abutment (h) is required to achieve good stability of the coupling. The methodology developed in this study is applicable to a variety of teeth, making it versatile and highly adaptable for broader clinical applications.